Assessment of developmental delay among children aged 0-3 years attending well baby clinic in a tertiary care hospital in South Chennai using TDSC (0-3 years) and LEST (0-3 years) - Jagannathan, Prahada; Narayanan, Rajeshwari; Nagarethinam, Divya Priyadarshini; Arunachalam , Savitha (International Journal of Contemporary Pediatrics, 2025)
Background: Global developmental delay can lead to long term impairment in academic performance, social interactions, and overall quality of life. Prevalence of global developmental delay ranges from 1-3%. Early identification and intervention of developmental delay limits disability and improves outcome. Methods: The aim of this cross-sectional study was assessment of developmental delay among children aged 0-3 years attending the well-baby clinic in Dr Kamakshi Memorial Hospital, a tertiary care pediatric centre in south Chennai using Trivandrum development screening chart (TDSC) (0-3 years) and Language evaluation scale Trivandrum (LEST) (0-3 years). We also aimed to describe the socio-demographic factors associated with developmental delay. Results: Developmental delay was defined as TDSC and/or LEST delay. 21 children out of 251 children had developmental delay i.e., TDSC and /or LEST delay. Prevalence of developmental delay in our study was 8.4%. 13 children (5.2%) had delay only in TDSC scale, 14 children (5.6%) had delay only using LEST scale and 6 children (2.4%) had delay in both TDSC and LEST. 7 children had only motor delay, 8 children had only language delay and 6 children had delay in both motor and language domains. IVF conception was found to have statistically significant association (p=0.002) with developmental delay. Conclusions: The prevalence of 8.4% developmental delay emphasizes need for early developmental screening programme as a routine clinical practice. Early recognition of developmental delay enables early intervention practices. It is recommended to use both TDSC and LEST scales for screening developmental delay in children.